Evaluasi Aplikasi Tokopedia Menggunakan Metode System Usability Scale (SUS) Dalam Pengadaan Barang Kantor - Z. Z. Bawazir; Santana, I P. A. A. (Jurnal Ilmiah Sains Sosial, Kewirausahaan dan Kebudayaan, 2025)
The use of e-commerce applications for office supplies procurement has been increasingly adopted by various organizations and companies. In this context, Tokopedia, as a leading e-commerce platform, plays a central role in optimizing procurement efficiency and providing access to a wide range of products. Assessing the usability and user experience when using Tokopedia for office supplies procurement is a crucial element. Utilizing the System Usability Scale (SUS) method, this research aims to provide insights into the extent to which Tokopedia meets user expectations. The results of this evaluation are expected to support application developers in improving the quality of the user experience and meeting high usability standards within the application. Furthermore, this research also benefits organizations considering the use of Tokopedia for their office supplies procurement, helping them make more data-driven decisions in selecting an e-commerce platform for their procurement needs. This research used the System Usability Scale (SUS) method to measure satisfaction levels. Questionnaires were given after the testing, where respondents were assigned tasks using the Tokopedia application. Subsequently, a questionnaire was provided to determine the final results. The results of the initial testing indicate a usability score for the Tokopedia application of 67.58%, which means it is close to the "Good" status but only reaches an "OK" level for the obtained results.